Kunskapens tider: Historiska perspektiv på kunskapssamhället - Elgán, Elisabeth; Sandén, Annika (Stockholm University Press, 2016)
Today's society is often characterized as a knowledge society, in contrast to the earlier industrial society. Historians however know that all societies are and have been knowledge societies. Without the ability to create, transfer, and use knowledge, between individuals and groups, power areas would neither have been built nor maintained. This edited volume reflects how historical actors, both those in power as well as laymen and officials, have produced and utilised information and knowledge from the Middle Ages until today. It acommodates research into census, urbanisation, history of kings and queens, exercise of public authority, social and political movements, disciplining and formation of opinion. In Kunskapens tider. Historiska perspektiv på kunskapssamhället ("The knowledge society. A historical perspective") nine researchers from the Department of History at Stockholm University contribute with examples of the need for and use of knowledge, in different historical situations and periods.